Caracterização e aplicação da farinha obtida do resíduo do processamento de acerola em massas alimentícias - Moreira, Renata Montarrôyos (2018)
The acerola (Malpighia emarginata DC.) contains high content of antioxidant substances such as vitamin C, carotenoids and phenolic compounds. The fruit in natura has limitations, both for its commercialization, due to its high perishability, and through its processing, where there is generation of residues (peel and seeds). Therefore, the production of flour from these residues presents itself as a viable alternative for its use, and its use in food products. The objective of the present research was to elaborate and analyze the physicochemical characteristics of the acerola residue flour (FRA) and its mixtures with durum wheat flour (FT), and to evaluate its viability in the application of pasta type Talharim, as the physicalchemical and technological characterization of the mass produced. Samples with flour mixtures contained percentages of 5%, 10%, 15% of acerola residue flour in relation to wheat flour, in addition to control samples (0% substitution) and 100% FRA sample. The partial replacement of wheat flour by FRA did not result in a significant alteration in the water content, lipids, protein, ashes, carbohydrates and total carotenoids in relation to the control sample (p>0.05). However, a decrease was observed in relation to the pH values, for coordinate of luminosity (L*) and coordinate b* (p<0.05). However, increase in acidity, vitamin C, phenolic compounds, coordinated a* and ?E (overall color difference) were observed with increased substitution (p<0.05). High fiber content was found in the acerola residue flour, with a value of 60.15% of total fiber, 53.79% of insoluble fiber and 6.36% of soluble fiber. For the pasta, the mixture of FT and FRA did not provide significant differences in the variables of water content, lipids, proteins, carbohydrates and energy (p>0.05). Reduction of the pH was observed, as well as for the color analysis, by means of the L* coordinate in which the samples became darker and the coordinate b* (p<0.05). Increase was identified with the substitution of FT by FRA in formulations with substitution in relation to the control formulation (F0), for ash content, acidity, vitamin C, phenolic compounds, carotenoids, a* and ?E coordinates. In relation to technological analysis, as the FRA substitutions were increased, a significant difference (p<0.05) was detected in the samples with substitution in relation to the control sample (0% substitution) for the cooking time, water absorption index, volume expansion, except for loss of soluble solids and instrumental texture in which there was no significant difference (p>0.05). For the sensory analysis, in general, when evaluated by the overall impression, all samples with substitution did not differ between them (p>0.05) and showed good sensory acceptance, evaluated as "slightly liked" and when evaluated by the intention of purchase, the F10 formulation was evaluated with a higher grade. In this sense, the elaboration of the acerola residue flour was a viable alternative for the durum wheat flour substitution, making it possible to substitute up to 15% for the elaboration of the Talharim type pasta.